Selective inhibition of Rhizopus eumelanin biosynthesis by novel natural product scaffold-based designs caused significant inhibition of fungal pathogenesis. Issue 13 (10th July 2020) - Soliman, Sameh S. M.; Hamdy, Rania; Elseginy, Samia A.; Gebremariam, Teclegiorgis; Hamoda, Alshaimaa M.; Madkour, Mohamed; Venkatachalam, Thenmozhi; Ershaid, Mai N.; Mohammad, Mohammad G.; Chamilos, Georgios; Ibrahim, Ashraf S.
Abstract : Melanin is a dark color pigment biosynthesized naturally in most living organisms. Fungal melanin is a major putative virulence factor of Mucorales fungi that allows intracellular persistence by inducing phagosome maturation arrest. Recently, it has been shown that the black pigments of Rhizopus delemar is of eumelanin type, that requires the involvement of tyrosinase (a copper-dependent enzyme) in its biosynthesis. Herein, we have developed a series of compounds (UOSC-1–14) to selectively target Rhizopus melanin and explored this mechanism therapeutically. The compounds were designed based on the scaffold of the natural product, cuminaldehyde, identified from plant sources and has been shown to develop non-selective inhibition of melanin production. While all synthesized compounds showed significant inhibition of Rhizopus melanin production and limited toxicity to mammalian cells, only four compounds (UOSC-1, 2, 13, and 14) were selected as promising candidates based on their selective inhibition to fungal melanin. The activity of compound UOSC-2 was comparable to the positive control kojic acid. The selected candidates showed significant inhibition of Rhizopus melanin but not human melanin by targeting the fungal tyrosinase, and with an IC50 that are 9 times lower than the reference standard, kojic acid. Furthermore, the produced white spores were phagocytized easily and cleared faster from the lungs of infected immunocompetent mice and from the human macrophages when compared with wild-type spores. Collectively, the results suggested that the newly designed derivatives, particularly UOSC-2 can serve as promising candidate to overcome persistence mechanisms of fungal melanin production and hence make them accessible to host defenses.